Brazil's Bolsa Escola Program : The Role of Local Governance in Decentralized Implementation - de Janvry, Alain (World Bank, Washington, DC, 2014)
This study analyzes the role of local governance in the implementation of Bolsa Escola, a decentralized conditional cash transfer program for child education in Brazil. It is based on a survey of 260 municipalities in four states of the Northeast. The analysis focuses on program implementation. Results show that there was considerable confusion over the municipality s role in beneficiary selection and consequently much heterogeneity in implementation across municipalities. Social control councils as direct accountability mechanisms were often not in place and poorly informed, weakening their role. However, electoral support for incumbent mayors rewarded larger program coverage, presence of councils, and low leakages of benefits to the non-poor.